Enhanced AAβ cryptosystem - a comparative analysis - Mahad, Zahari; Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
A major enhancement strategy of the AAβ cryptosystem is currently proposed which incorporates the Rabin-p decryption method upon its original design while maintaining the key generation and encryption procedures. Consequently, such strategy improved the decryption procedure of the AAβ cryptosystem compare to any previously proposed design. In this paper, the aim is to provide a comparative analysis of the new design of the AAβ cryptosystem with the original and the other enhancement methods in existence. The scope of this work is a comparative analysis upon the decryption procedure only. The results show that the enhanced version of the AAβ cryptosystem is efficient in term of faster running time and lower memory consumption.